Nobody's baby: The politics and perceptions of informal housing in Alexandra Township - Lucas, Justine (My University, 1996)
In late February 1996, a group of property-owners in northern Johannesburg attacked residents of a squatter camp that had sprung up on their doorstep, and burnt down several shacks. Local government officials, while not condoning the action, promised to relocate the squatters to another site. The squatters, who were not told where they would be rehoused, refused to move, prompting further threats from the enraged property-owners. On April 29, there was an attempt to move the squatters to Diepsloot, far from their current homes and jobs. They resisted, and in the ensuing struggle police fired teargas and rubber bullets. This has been a familiar story over the last decade, as local government battled against endless waves of 'land invasions' while a new democratic dispensation was being negotiated, and mainly white property-owners protested against the rising crime and drop in property prices that they feared would result from informal settlement. But there is a twist to this tale. In 1996, two years after South Africa's first democratic election brought in a new housing policy, and several months after local government was elected to provide urban municipal services, the angry property-owners in the above account are residents of Alexandra township's East Bank suburb. Many of them are members of the ANC, and are represented by the ANC-aligned East Bank Civic Association. The local government officials who have promised to remove the squatters are also mainly ANC members; several of them former civic activists from Alexandra who championed the rights of squatters in the 1980s. As a 'squatter township' Alexandra is different both from the rest of Johannesburg's northern suburbs and from most other townships or informal settlements. This difference is a legacy of its anomalous history as a 'location' - a formerly freehold area where property rights were granted a year before the introduction of the 1913 Land Act, and which survived the demolitions and removals meted out to other similar areas like Sophiatown and Western Native Township. Although usually described as a township, Alexandra predates the development of these vast, regulated and uniform 'satellite towns', far from white areas, which were designed to house and control the African workforce. For a significant portion of its history, Alexandra fell outside municipal authority and remained free of much apartheid legislation. As an overcrowded and crime-ridden slum, Alexandra was 'Nobody's Baby'- situated in the heart of Johannesburg's northern suburbs, but too much of a liability for white municipalities to take responsibility for. The modernist conceptions of planning that underpinned apartheid thus largely failed to gain purchase in Alexandra. ...In this paper I look at how contestations over the representation of space in Alexandra have been shaped by the failure of apartheid's racial modernism, and explore the historical roots of current perceptions of informal housing as a problem for planners.
African Studies Seminar series. Paper presented 13 May 1996
Keywords: Blacks. Housing. South Africa. Alexandra; Housing. South Africa. Alexandra